ROYAL AIR FORCE 1939-1945 - Cornwell, Richard (Scientia Militaria - South African Journal of Military Studies, 2011)
This three volume official history of the Royal Air Force in World War II was first published in 1953 to satisfy the need for a brief, interim history until such time as a fuller, more analytical treatment could be attempted. In the event the Royal Air Force was not dealt with as a separate entity in the massive official History of the Second World War edited by J. R. M. Butler, except for the four volumes published on the strategic air offensive. In view of this Her Majesty's Stationery Office has taken the welcome decision to re-issue this work by Richards and Saunders, with some minor textual emendations.